Revealing the Roles of MOAP1 in Diseases: A Review - Yanfang Su; Weixia Wang; Xianfang Meng (Cells, 2022)
Modulator of apoptosis protein1 (MOAP1), also known as MAP1 and PNMA4, belongs to the PNMA gene family consisting of at least 15 genes located on different chromosomes. MOAP1 interacts with the BAX protein, one of the most important apoptosis regulators. Due to its critical role in a few of disease-associated pathways, MOAP1 is associated with many diseases such as cancers and neurological diseases. In this study, we introduced MOAP1 and its biological functions and reviewed the associations between MOAP1 and a few diseases including cancers, neurological diseases, and other diseases such as inflammation and heart diseases. We also explained possible biological mechanisms underlying the associations between MOAP1 and these diseases, and discussed a few future directions regarding MOAP1, especially its potential roles in neurodegenerative disorders. In summary, MOAP1 plays a critical role in the development and progression of cancers and neurological diseases by regulating a few genes related to cellular apoptosis such as BAX and RASSF1A and interacting with disease-associated miRNAs, including miR-25 and miR1228.